Gender Differences in Outcomes of ST Elevation Myocardial Infarction undergoing Primary Percutaneous Coronary Intervention - Raja, Tanvir Ahmad; Husnain Yousaf; Abair ul Haq; Shafiq ur Rehman; Sheraz, Ephraim (Indus Journal of Bioscience Research, 2025)
Introduction: Despite the growing use of technology and clinical process improvement initiatives in the field of cardiology, particularly on the utilization of PPCI, the number of STEMI and its results by gender have remained unchanged. There are always disparities where women receive their treatments later than men and have poorer results than men. Objectives: To compare the clinical outcome, complications, and procedural success of STEMI patients across gender and evaluate the difference in gender for PPCI in a hospital setting in Pakistan. Materials and Methods: This hospital-based, observational study reviewed 300 patients with STEMI who underwent PPCI for six months. The collected demographic characteristics, procedural data points, and longitudinal results were compiled and compared for sexually dimorphic analyses. Results: Compared to male patients, female patients were younger, had more comorbids, and experienced longer delays to PPCI. Bleeding and in-hospital mortality increased in women through procedural complications. Multivariate analysis also showed that age and late PPCI are predictors of adverse outcomes in female patients. Conclusion: The outcomes of STEMI for men and women remain significantly different, and gender considerations should be maintained when considering optimal interventions, awareness, and equal treatment for both genders.